Oral communications of speech language pathologists in a clinical setting - Leela Koran (Journal of Modern Languages)
This paper reports on a study that attempts to describe the oral communication of Speech-Language Pathologists (SLP) in a clinical setting within a multicultural society and addresses, to some extent, the problem of lack of research on SLP practice in Malaysia.